Applied Econometrics: theory and empirical illustrations - Ezie, Obumneke; Ezie, Progress K. (Kaduna, Nigeria Kabod Limited, 2021)
The book is divided into three parts, with ten chapters. The first four chapters constitute part one, which basically provides the background, correlation and classical linear regression model. The part two comprises the second four parts which discusses time series econometrics. The third part consists of chapter ten which deals with panel data econometrics.
Includes bibliography
osc 14/01/2014
Loans
Keywords: Econometrics